2014
DOI: 10.1016/j.drugalcdep.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of prison-initiated buprenorphine: Prison outcomes and community treatment entry

Abstract: Background Buprenorphine is a promising treatment for heroin addiction. However, little is known regarding its provision to pre-release prisoners with heroin dependence histories who were not opioid-tolerant, the relative effectiveness of the post-release setting in which it is provided, and gender differences in treatment outcome in this population. Methods This is the first randomized clinical trial of prison-initiated buprenorphine provided to male and female inmates in the US who were previously heroin-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
106
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 37 publications
(61 reference statements)
1
106
1
2
Order By: Relevance
“…Buprenorphine appears to be much easier to divert during treatment than methadone because it must be administered sublingually, and if diversion is to be minimized, the patient must be observed for 5–10 minutes until the dose is absorbed (in tablet or film form). A study using buprenorphine in a Maryland prison with sentenced prisoners expected to be released within several months found that more than 10% of participants attempted to divert the medication and hence were discontinued from receiving the medication [60]. This rate of attempted buprenorphine diversion was similar to that found by Magura and colleagues in a study at Rikers Island comparing methadone to buprenorphine treatment for sentenced jail inmates [21].…”
Section: 0 Discussionsupporting
confidence: 58%
“…Buprenorphine appears to be much easier to divert during treatment than methadone because it must be administered sublingually, and if diversion is to be minimized, the patient must be observed for 5–10 minutes until the dose is absorbed (in tablet or film form). A study using buprenorphine in a Maryland prison with sentenced prisoners expected to be released within several months found that more than 10% of participants attempted to divert the medication and hence were discontinued from receiving the medication [60]. This rate of attempted buprenorphine diversion was similar to that found by Magura and colleagues in a study at Rikers Island comparing methadone to buprenorphine treatment for sentenced jail inmates [21].…”
Section: 0 Discussionsupporting
confidence: 58%
“…This paradoxical ability to describe this cycle of addiction with incarceration and a lack of recognition that “being in a controlled setting” like prison, jail or even in a voluntary drug treatment program where they undergo supervised withdrawal from opioids, is consistent with the new qualifier to the Fifth Edition of the Diagnostic and Statistical Manual definition of having an opioid use disorder (American Psychiatric Association, 2013). Future framing of having an opioid use disorder in this manner will be crucial for expanding OAT in community settings, but also to motivate PWIDs to either continue (Rich et al, 2015) or initiate it during periods of confinement (Dolan et al, 2005; Gordon et al, 2014; Kinlock et al, 2009; Larney, Toson, Burns, & Dolan, 2012; Macalino et al, 2004) in order to optimize health post-release, whether to reduce overdose (Hedrich et al, 2012; Kinner et al, 2012) or improve HIV treatment outcomes (Springer et al, 2010; Springer et al, 2012)…”
Section: Discussionmentioning
confidence: 99%
“…At the time of incarceration, identifying individuals who receive methadone in the community, confirming methadone dosages, and rapidly reinitiating treatment presents a logistical challenge; however participants reported that security staff was inattentive to their needs, so better training and reporting protocols could have an impact. Additionally, because of the evidence supporting initiation of methadone or buprenorphine prior to release from prison, if methadone is not offered to individuals with long sentences, at least reinitiating MAT before release could improve rates of treatment entrance in the community (Rich et al, 2015; Gordon et al, 2014; Kinlock et al, 2007). …”
Section: Discussionmentioning
confidence: 99%